Autoimmune Hemolytic Anemia Causing Group 5 Pulmonary Hypertension: A Rare Case - Muchammad Dzikrul Haq Karimullah; Hiradipta Ardining (Heart Science Journal, 2020)
Pulmonary hypertension (PH)has been associated with hemolytic anemia. The prevalence of PH in hemolytic anemia is estimated to be as high as 10-40%, and reportsarepresenting poor prognosis in this subset of patients. PH associated with autoimmune hemolytic anemia (AIHA) is still rarely discussed,and there is paucity of literature regarding its precise pathophysiology and treatment. Here, we describe a case of PH associated with AIHA. A 34-year old woman came to our center with chief complaint of dyspnea on exertion. She was previously diagnosed with AIHA with positive direct Coomb's test. Physical examination, chest X-ray and echocardiography were consistent with pulmonary hypertension. The diagnosis of group 5 pulmonary hypertension was made. Although rare, the association between chronic hemolytic anemia and PH is evident, through several mechanisms involving nitric oxide inactivation, direct injury oftheendothelium, oxidative damage, thromboembolic formation, and left ventricular dysfunction. The management of PH in hemolytic disorders comprises treatment of underlying hemolytic disorder and PH-specific therapies. For PH specific therapy, to date, there are no therapies that have been fully studied for these specific patient population. Our patient was given bisoprolol, furosemide, amlodipine, spironolactone, candesartan, beraprost sodium and sildenafil. On follow up twomonths later, her functional status was improved. In summary, PH associated with AIHA develop via multifactorial and complex mechanisms. PH in AIHA could be detected with meticulous history taking, physical examination, chest X-ray and echocardiography, and treatment with vasodilating agents were shown to improve the PH.